Assessment of physicochemical parameters for the drinking water quality in the vicinity of Nawabshah City, Sindh, Pakistan - Mangi, Sajjad Ali; Sohu, Samiullah; Soomro, Faheem Ahmed; Abdullah, Abd Halid; Nagapan, Sasitharan (ESTIRJ, 2017)
Quality of water may differ according to the geography of the region, due to that the quality of water is big concern worldwide, because majority of disease caused by the poor quality of drinking water. Subsequently realizing the significance of drinking water quality with in the central part of the Sindh province, this research work was carried out to assess the drinking water quality within the Nawabshah city, where the single source of supply water is the Gajrawah after the conventional treatment through the open ponds. In this study seven physicochemical parameter were investigated and laboratorial investigations demonstrated that the pH values were found with the WHO limits, TDS & EC values were found within the acceptable limits, except in one residential area, Turbidity was also high at all the locations only one area (Marium road colony) was found within the standards, furthermore, the hardness was present in all the samples at all the locations, which indicate that the water supplied to public was hard in nature. In addition to that Temperature and Dissolved Oxygen were found safe and within the limits and it was concluded that the water supplied to residents of the inspected areas were found not fit for drinking and it is suggested that the water supply, should be improved and essential steps should be taken to treat the water.